Current collector and preparation method thereof, pole piece, battery and electric device

By using a roughened surface composed of nanoparticles in the current collector of lithium-ion batteries, the bonding force and contact area between the active material and the current collector are improved, and the problem of degradation of cycle stability of lithium-ion batteries is solved and higher cycle stability is achieved.

CN119542427APending Publication Date: 2025-02-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311122857.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During the circulation process of lithium-ion batteries, the volume of the electrode material expands and contracts due to the insertion and removal of lithium ions in the electrode material, resulting in a decrease in the binding force of the active material and the current collector, which leads to a sharp decline in circulation stability.

Method used

A current collector is used, which includes a copper foil body, and at least one side of the copper foil body is provided with a roughened surface composed of nanoparticles, and the nanoparticles include CuX, wherein X is Cl, Br or I. The current collector realizes roughening of the sides of the copper foil body by setting the modification layer, improves the bonding force and contact area between the active material and the current collector, reduces interface resistance and polarization, and improves cyclic stability performance.

Benefits of technology

It effectively improves the binding force and contact area between the active material and the current collector, reduces the interface resistance and polarization, and significantly improves the cycling stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542427A_ABST
    Figure CN119542427A_ABST
Patent Text Reader

Abstract

The invention provides a current collector, a pole piece, a battery and an electric device, and relates to the field of batteries. The current collector comprises a copper foil body, at least one side of the copper foil body is provided with a roughened surface formed by nano-particles, the nano-particles comprise CuX, and X is at least one of Cl, Br and I. After the current collector is used in the battery, the cycling stability of the battery can be improved, and the service life of the battery can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a current collector, a pole piece, a battery and an electrical device. Background Art

[0002] During the cycle of lithium-ion batteries, as lithium ions are continuously embedded in and extracted from active materials, the volume of the electrode material will continue to expand and contract, causing it to collapse or differentiate, resulting in the active material's bond with the current collector becoming increasingly poor, and easily falling off the current collector, causing the cycle stability of the lithium-ion battery to drop sharply. Summary of the invention

[0003] In view of the above problems, the present application provides a current collector, an electrode, a battery and an electrical device, which can improve the technical problem of poor battery cycle stability.

[0004] In a first aspect, an embodiment of the present application provides a current collector, which includes: a copper foil body, at least one side of which is provided with a roughened surface composed of nanoparticles, the nanoparticles include CuX, wherein X is at least one of Cl, Br, and I.

[0005] The current collector provided in the present application, on the one hand, uses the setting of the modified layer to roughen the side of the copper foil body, thereby effectively improving the binding force and contact area between the active material and the current collector, so that the active material can be stably bound to the current collector, reducing the interface resistance between the active material and the current collector, reducing polarization, and improving the cycle stability performance. On the other hand, the nano-scale CuX has a large specific surface area, which is conducive to charge transfer, and CuX (wherein X is at least one of Cl, Br, and I) is a p-type semiconductor with a near-ultraviolet band gap (2.9-3.1eV), a high hole mobility (0.4-12cm in polycrystalline thin film), and a high charge transfer rate (0.4-12cm in polycrystalline thin film). 2 V -1 s -1 ) and transparency in the visible light region, which helps to reduce impedance and further improve cycle stability.

[0006] In some embodiments, the particle size of the nanoparticles is 400-1000 nm, and can be 400-700 nm. Within the above particle size range, the nanoparticles have a larger specific surface area, which is more conducive to charge transfer and effectively improves cycle stability.

[0007] In some embodiments, the height of the nanoparticles is 250-1520 nm, and can be 320-840 nm. The nanoparticles within the above height range have a stable structure, which can enable the active material to be stably combined with the current collector, thereby improving the cycle stability performance.

[0008] In some embodiments, one side of the copper foil body is a matte surface, and the other side is a roughened surface. With the above arrangement, a double-sided roughened surface current collector with one roughened surface and one matte surface is obtained, which is conducive to the stable bonding of active materials to the current collector and improves cycle stability.

[0009] In some embodiments, the roughness of the roughened surface is greater than that of the matte surface, and the difference in roughness between the roughened surface and the matte surface is: ΔRa≤0.196μm, ΔRz≤0.226μm, ΔRq≤1.622μm; ΔRa≤0.136μm, ΔRz≤0.177μm, ΔRq≤0.883μm; and ΔRa≤0.113μm, ΔRz≤0.087μm, ΔRq≤0.474μm. By controlling the roughness within the above range, it is beneficial to improve the cycle stability.

[0010] In some embodiments, the roughness of the roughened surface is: Ra: 0.784-0.936 μm, Rz: 0.928-1.116 μm, Rq: 3.272-4.876 μm. Within the above roughness range, the bonding force and contact area between the active material and the current collector can be effectively improved, so that the active material can be stably bonded to the current collector, and the cycle stability performance is improved.

[0011] In some embodiments, both sides of the copper foil body are provided with roughened surfaces. The use of both sides being roughened surfaces to obtain a double-sided roughened current collector is beneficial for the active material to be stably bonded to the current collector and improve the cycle stability.

[0012] In some embodiments, the roughness difference between the roughened surfaces on both sides is maintained at: ΔRa≤0.03μm, ΔRz≤0.04μm, ΔRq≤0.4μm. Maintaining the roughness difference between the roughened surfaces on both sides within the above range can avoid imbalance in charge and discharge cycle life, thereby improving cycle stability.

[0013] In some embodiments, the copper foil body has a thickness of 6-20 μm.

[0014] In a second aspect, the present application provides a method for preparing the current collector in the above embodiment, which comprises: forming nanoparticles on at least one side of a copper foil body as a roughened surface.

[0015] The above preparation method is simple and controllable to operate, and does not affect the strength of the copper foil body itself.

[0016] In some embodiments, nanoparticles are grown in-situ in a liquid phase on at least one side of the copper foil body.

[0017] The liquid phase in-situ growth method is controllable and easy to industrialize, and the prepared nanoparticles are firmly bonded to the copper foil body, which is conducive to the long-term and stable bonding between the active material layer and the current collector, effectively improving the cycle performance.

[0018] In some embodiments, at least one side of the copper foil body is immersed in a reaction solution for liquid phase reduction reaction; wherein the reaction solution comprises: a mixed aqueous solution of 0.4-1.2 mol / L CuSO4 and 0.01-0.04 mol / L 1-butyl-3-methylimidazole halide.

[0019] The above-mentioned liquid phase reduction reaction method can effectively reduce the use of various acid and alkali pretreatment steps for commercial copper foil, reduce production costs and generate no waste acid and alkali, and has excellent deposition uniformity and processability. The deposition phase transition can be achieved by replacing a single ingredient in the formula, which is convenient for industrial production.

[0020] Optionally, the temperature of the liquid phase reduction reaction is 25-50° C., and the time of the liquid phase reduction reaction is 10-60 min.

[0021] In a third aspect, the present application provides a pole piece, which includes a current collector in the above embodiment and an active material layer arranged on the surface of the current collector.

[0022] In a fourth aspect, the present application provides a battery, which includes the battery cell in the above embodiment.

[0023] In a fifth aspect, the present application provides an electrical device, which includes the battery in the above embodiment, and the battery is used to provide electrical energy.

[0024] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0026] Figure 1 A schematic diagram of the structure of a vehicle according to some embodiments of the present application;

[0027] Figure 2 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;

[0028] Figure 3 A schematic diagram of the exploded structure of a battery cell according to some embodiments of the present application;

[0029] Figure 4 This is a schematic diagram of the structure of the pole piece of some embodiments of the present application;

[0030] Figure 5 A schematic diagram of the structure of a current collector preparation system in some embodiments of the present application;

[0031] Figure 6 A scanning electron microscope and element distribution diagram of the roughened surface of the current collector provided in Example 1 of the present application;

[0032] Figure 7 for Figure 6 Cross-sectional SEM image of the center current collector;

[0033] Figure 8 It is a schematic diagram of the electrochemical impedance spectroscopy test results of Example 1 and Comparative Example 1 of the present application;

[0034] Fig. 9 A scanning electron microscope and element distribution diagram of the roughened surface of the current collector provided in Example 3 of the present application;

[0035] Fig.10 A scanning electron microscope and element distribution diagram of the roughened surface of the current collector provided in Example 4 of the present application;

[0036] Fig.11 Schematic diagram of the cyclic stability provided for this application.

[0037] The reference numerals in the specific implementation manner are as follows:

[0038] 1000-Vehicles;

[0039] 100-battery; 200-controller; 300-motor;

[0040] 10-box; 11-first part; 12-second part;

[0041] 20 - battery cell; 21 - end cap; 21a - electrode terminal; 22 - housing; 23 - electrode assembly;

[0042] 24-pole piece; 241-current collector; 242-active material layer;

[0043] 30 - current collector preparation system; 31 - copper foil; 32 - unwinding mechanism; 33 - soaking mechanism; 34 - cleaning mechanism; 35 - drying mechanism; 36 - winding mechanism. DETAILED DESCRIPTION

[0044] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0046] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0047] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0048] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0049] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0050] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0051] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0052] During the cycle of lithium-ion batteries, as lithium ions are continuously embedded in and extracted from electrode materials, the volume of the electrode materials will continue to expand and contract, causing them to collapse or differentiate, resulting in the electrode material's bond with the current collector becoming increasingly poor, making it easy to fall off the current collector, causing the cycle stability of the lithium-ion battery to drop sharply.

[0053] In order to improve the cycle stability of the battery, the present application provides a current collector, which includes: a copper foil body, the copper foil body has two opposite sides, at least one of which is provided with a modified layer, the modified layer is composed of nanoparticles, the surface of the modified layer is a rough surface, and the nanoparticles include CuX, wherein X is Cl, Br or I.

[0054] In such a current collector, on the one hand, the modification layer is used to roughen the side of the copper foil body, thereby effectively improving the bonding force and contact area between the active material and the current collector, so that the active material can be stably bonded to the current collector, reducing the interface resistance between the active material and the current collector, reducing polarization, and improving the cycle stability performance. On the other hand, the nanoscale CuX has a large specific surface area, which is conducive to charge transfer, and CuX (where X is at least one of Cl, Br, and I) is a p-type semiconductor with a near-ultraviolet band gap (2.9-3.1 eV), a high hole mobility (0.4-12 cm in polycrystalline thin films), and a high charge transfer rate (0.4-12 cm in polycrystalline thin films). 2 V -1 s -1 ) and transparency in the visible light region, which is conducive to further improving the cycle stability.

[0055] The battery cells disclosed in the embodiments of the present application can be used in, but not limited to, electrical devices such as vehicles, ships or aircraft. A power supply system comprising the battery cells and batteries disclosed in the present application can be used to form the electrical device, which is beneficial to improving the stability of battery performance and battery life.

[0056] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0057] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.

[0058] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.

[0059] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0060] In the present application, the battery 100 refers to a single physical module including one or more battery cells 20 to provide a certain voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The battery 100 may also include a box 10 for encapsulating one or more battery cells 20, and the box 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.

[0061] Please refer to Figure 2 , Figure 2An exploded view of a battery 100 provided in some embodiments of the present application. The battery 100 includes a box 10 and a battery cell 20, and the battery cell 20 is contained in the box 10. Among them, the box 10 is used to provide a storage space for the battery cell 20, and the box 10 can adopt a variety of structures. In some embodiments, the box 10 may include a first part 11 and a second part 12, the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 may be a hollow structure with one end open, the first part 11 may be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 may also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the box 10 formed by the first part 11 and the second part 12 may be in a variety of shapes, such as a cylinder, a cuboid, etc.

[0062] In the battery 100, there may be multiple battery cells 20, and the multiple battery cells 20 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 20 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 20.

[0063] Each battery cell 20 may be a secondary battery or a primary battery. The battery cell 20 may be cylindrical, flat, rectangular or in other shapes.

[0064] Please refer to Figure 3 , Figure 3 The schematic diagram of the exploded structure of the battery cell 20 provided in some embodiments of the present application. The battery cell 20 refers to the smallest unit that constitutes the battery. Figure 3 The battery cell 20 includes an end cover 21, a shell 22, an electrode assembly 23 and other functional components.

[0065] The end cap 21 refers to a component that covers the opening of the shell 22 to isolate the internal environment of the battery cell 20 from the external environment. Without limitation, the shape of the end cap 21 can be adapted to the shape of the shell 22 to match the shell 22. Optionally, the end cap 21 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 21 is not easily deformed when squeezed and collided, so that the battery cell 20 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 21a can be provided on the end cap 21. The electrode terminal 21a can be used to electrically connect to the electrode assembly 23 for outputting or inputting electrical energy of the battery cell 20. In some embodiments, the end cap 21 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold. The material of the end cap 21 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member may be provided inside the end cap 21, and the insulating member may be used to isolate the electrical connection components in the housing 22 from the end cap 21 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.

[0066] The shell 22 is a component used to cooperate with the end cap 21 to form the internal environment of the battery cell 20, wherein the formed internal environment can be used to accommodate the electrode assembly 23, the electrolyte and other components. The shell 22 and the end cap 21 can be independent components, and an opening can be set on the shell 22, and the internal environment of the battery cell 20 is formed by covering the opening with the end cap 21 at the opening. Without limitation, the end cap 21 and the shell 22 can also be integrated. Specifically, the end cap 21 and the shell 22 can form a common connection surface before other components are put into the shell, and when the interior of the shell 22 needs to be encapsulated, the end cap 21 covers the shell 22. The shell 22 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 22 can be determined according to the specific shape and size of the electrode assembly 23. The material of the shell 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0067] The electrode assembly 23 is a component where electrochemical reactions occur in the battery cell 20. The housing 22 may contain one or more electrode assemblies 23. The electrode assembly 23 is mainly formed by winding or stacking pole pieces 24 (i.e., positive pole pieces and negative pole pieces) with opposite electrical properties and a separator between the pole pieces 24 with opposite electrical properties to isolate them, and the pole ears of each pole piece 24 are connected to the electrode terminal to form a current loop.

[0068] See also Figure 4According to some embodiments of the present application, the present application provides a pole piece 24 , which includes a current collector 241 and an active material layer 242 disposed on a surface of the current collector 241 .

[0069] The current collector 241 refers to a structure or component for collecting current.

[0070] The active material layer 242 refers to a film layer containing active materials, wherein the current collector 241 includes two opposite surfaces in its own thickness direction. The active material layer 242 can be provided on any one of the two opposite surfaces of the current collector 241, or can be provided on both opposite surfaces of the current collector 241.

[0071] When the electrode sheet 24 is a negative electrode sheet, the active material layer 242 is a negative electrode active material layer, and the negative electrode active material contained in the negative electrode active material layer may include one or more of carbon-based active materials, titanium-based active materials, silicon-based active materials, nitrides, metallic lithium, etc. As an example, the carbon-based material may include one or more of graphite, hard carbon, soft carbon, mesophase carbon microspheres, graphene, etc.; in the exemplary embodiment, the titanium-based active material includes one or more of lithium titanate, titanium dioxide, etc.; as an example, the silicon-based active material includes one or more of silicon, silicon dioxide, etc.; as an example, the nitride includes lithium nitride, etc.

[0072] When the electrode sheet 24 is a positive electrode sheet, the active material layer 242 is a positive electrode active material layer, and the positive electrode active material contained in the positive electrode active material layer may include one or more of metal inorganic active materials and organic active materials. As an example, the metal inorganic active material may include one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium manganese oxide, nickel cobalt manganese iron lithium, nickel cobalt aluminum oxide, etc. As an example, the organic active material may include one or more of quinone compounds, carboxylate compounds, anhydride compounds, amide compounds, etc.

[0073] Regardless of whether the electrode sheet is a positive electrode sheet or a negative electrode sheet, the active material layer 242 includes a binder in addition to the active material, or may further include components such as a conductive agent and other additives.

[0074] As an example, the binder includes but is not limited to one or more of an oil-soluble binder, a water-soluble binder, an emulsion-type binder, etc. As an example, the oil-soluble binder includes one or more of polyvinylidene fluoride, polyimide, polytetrafluoroethylene, polybutyl acrylate, polyacrylonitrile, etc.; as an example, the water-soluble binder includes one or more of carboxymethyl cellulose, carboxymethyl cellulose salt, polyacrylic acid, polyacrylic acid salt, polyvinyl alcohol, sodium alginate, cyclodextrin, etc.; as an example, the emulsion-type binder includes one or more of styrene-butadiene rubber, vinyl acetate resin, acrylic resin, and chlorinated rubber.

[0075] As an example, the conductive agent includes but is not limited to one or more of acetylene black (SP), carbon nanotubes, conductive carbon black (super-P), Ketjen black, carbon fiber, graphene, and the like.

[0076] As an example, other additives include but are not limited to functional components such as lithium supplements.

[0077] The above-mentioned positive electrode active material, negative electrode active material, binder, conductive agent and other materials can be specifically selected according to the application or production requirements of the electrode.

[0078] According to some embodiments of the present application, the current collector includes a copper foil body, at least one side of the copper foil body is provided with a roughened surface composed of nanoparticles, the nanoparticles include CuX, wherein X is at least one of Cl, Br, and I.

[0079] It should be noted that the copper foil body can be a copper foil, or a composite layer with a polymer layer in the middle, and both sides of the polymer in the thickness direction are copper foils, in which case the current collector is a composite current collector. It can be understood that when the copper foil body is a composite layer, the copper foil body has two opposite sides along its thickness direction, which means the two sides of the entire composite layer in the thickness direction, and at least one side of the composite layer in the thickness direction is provided with a roughened surface composed of nanoparticles.

[0080] The roughened surface refers to a surface where nanoparticles form a concavo-convex structure on the surface of the copper foil body, and the surface of the concavo-convex structure constitutes the roughened surface.

[0081] Nanoparticles refer to particles whose particle size is at the nanometer level, that is, their particle size is ≤1 μm.

[0082] The nanoparticles include CuX, wherein X is at least one of Cl, Br, and I, which means that the nanoparticles are at least one of CuCl, CuBr, and CuI, and can be any one of CuCl, CuBr, and CuI.

[0083] The current collector provided in the present application, on the one hand, uses the setting of the modified layer to roughen the side of the copper foil body, thereby effectively improving the binding force and contact area between the active material and the current collector, so that the active material can be stably bound to the current collector, reducing the interface resistance between the active material and the current collector, reducing polarization, and improving the cycle stability performance. On the other hand, the nano-scale CuX has a large specific surface area, which is conducive to charge transfer, and CuX (wherein X is at least one of Cl, Br, and I) is a p-type semiconductor with a near-ultraviolet band gap (2.9-3.1eV), a high hole mobility (0.4-12cm in polycrystalline thin film), and a high charge transfer rate (0.4-12cm in polycrystalline thin film). 2 V -1 s -1) and transparency in the visible light region, which is conducive to further improving the cycle stability.

[0084] According to some embodiments of the present application, the particle size of the nanoparticles is 400-1000 nm.

[0085] The method for measuring the particle size of nanoparticles includes: collecting and obtaining an electron microscope image of the roughened surface, and obtaining the particle size of the nanoparticles according to the electron microscope image, that is, the particle size at this time is a planar particle size. The electron microscope image includes but is not limited to a scanning electron microscope image.

[0086] Within the above particle size range, the nanoparticles have a larger specific surface area, which is more conducive to charge transfer and effectively improves the cycle stability performance.

[0087] As an example, the particle size of the nanoparticles is any value of 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm, 480nm, 490nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm or between any two values.

[0088] Optionally, the particle size of the nanoparticles is 400-800 nm, further optionally 400-700 nm.

[0089] According to some embodiments of the present application, the height of the nanoparticles is 250-1520 nm.

[0090] The method for measuring the height of the nanoparticles includes: collecting and obtaining an electron microscope image of a cross section of the current collector in the thickness direction, and obtaining the connection interface between the nanoparticles and the current collector and the straight-line distance to the side of the nanoparticles away from the current collector as the height according to the electron microscope image, that is, the height of the nanoparticles is actually the size of the nanoparticles in the thickness direction of the current collector. The electron microscope image includes but is not limited to a scanning electron microscope image.

[0091] The nanoparticle structure within the above height range is stable, which enables the active material to be stably combined with the current collector, thereby improving the cycle stability performance.

[0092] As an example, the height of the nanoparticles is any value of 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1300nm, 1500nm, 1520nm or between any two values.

[0093] Optionally, the nanoparticles have a height of 320-840 nm.

[0094] Due to the limitations of production processes and preparation technologies, the electrolytic copper foil currently produced is often an asymmetric metal substrate with a smooth surface on one side (the side in contact with the cathode roller) and a rough surface on the other side. This situation can easily cause the adhesion of large-scale coated active materials on the substrate surface to be inconsistent, resulting in differences in the two sides of the coating, and then causing inconsistency in the battery cells. Therefore, electrolytic copper foil with a smooth surface on one side and a rough surface on the other side can be used as the raw material, and its smooth surface can be roughened to reduce the difference between the two sides, avoid inconsistency in the battery cells, and improve the cycle performance.

[0095] Therefore, according to some embodiments of the present application, one side of the copper foil body is a matte surface, and the other side is a roughened surface.

[0096] It can be understood that the rough surface refers to a surface with a greater roughness than the smooth surface. The rough surface can be directly formed by electrolytic copper or the like, or roughened by physical grinding, etching or the like, so that the surface does not introduce any substances other than copper except for industrially acceptable impurities.

[0097] By using the above arrangement, a double-sided roughened current collector with one side roughened and the other side roughened is obtained, which is beneficial for the active material to be stably combined with the current collector and improves the cycle stability.

[0098] According to some embodiments of the present application, the roughness of the roughened surface is greater than the roughness of the rough surface, and the difference in roughness between the roughened surface and the rough surface is: ΔRa≤0.196μm, ΔRz≤0.226μm, ΔRq≤1.622μm.

[0099] It can be understood that since the roughness of the roughened surface is greater than that of the matte surface, ΔRa is the Ra of the roughened surface minus the Ra of the matte surface; ΔRz is the Rz of the roughened surface minus the Rz of the matte surface; and ΔRq is the Rq of the roughened surface minus the Rq of the matte surface.

[0100] By controlling the roughness within the above range, it is beneficial to improve the cycle stability.

[0101] As an example, ΔRa is any value among 0.01μm, 0.1μm, 0.11μm, 0.13μm, 0.15μm, 0.17μm, 0.196μm, etc., ΔRz is any value among 0.02μm, 0.05μm, 0.08μm, 0.11μm, 0.15μm, 0.17μm, 0.20μm, 0.226μm, etc., and ΔRq is any value among 0.1μm, 0.4μm, 0.8μm, 0.11μm, 0.16μm, 0.1622μm, etc.

[0102] Optionally, ΔRa≤0.136μm, ΔRz≤0.177μm, and ΔRq≤0.883μm.

[0103] Further optionally, ΔRa≤0.113 μm, ΔRz≤0.087 μm, and ΔRq≤0.474 μm.

[0104] According to some embodiments of the present application, the roughness of the roughened surface is: Ra: 0.784-0.936 μm, Rz: 0.928-1.116 μm, Rq: 3.272-4.876 μm.

[0105] Surface roughness parameters Rz (average peak-to-valley depth), Ra (arithmetic mean roughness), Rq (root mean square roughness). Refer to GB / T 1031-2009 "Surface roughness parameters and their values ​​of surface structure profile method" and use a surface roughness measuring instrument to measure the surface roughness parameters.

[0106] Within the above roughness range, the bonding force and contact area between the active material and the current collector can be effectively improved, so that the active material can be stably bonded to the current collector, thereby improving the cycle stability performance.

[0107] According to some embodiments of the present application, both sides of the copper foil body are provided with roughened surfaces.

[0108] The double-sided roughened surface of the current collector is used to obtain a double-sided roughened surface, which is beneficial for the active material to be stably bonded to the current collector and improve the cycle stability.

[0109] According to some embodiments of the present application, the difference in roughness between the roughened surfaces on both sides is maintained as follows: ΔRa≤0.03 μm, ΔRz≤0.04 μm, ΔRq≤0.4 μm.

[0110] The difference in roughness of the roughened surfaces on both sides is maintained within the above range, and the structures on both sides are basically symmetrically arranged, which is not only conducive to making the contact resistance of the active material layers on both sides symmetrical and the capacity on both sides released evenly, but also the bonding strength on both sides is basically consistent, avoiding imbalance in the charge and discharge cycle life, thereby improving the cycle stability.

[0111] According to some embodiments of the present application, the copper foil body has a thickness of 6-20 μm.

[0112] Within the above range, the copper foil body has better toughness and strength, which is beneficial to improving the cycle stability.

[0113] As an example, the thickness of the copper foil body is any value of 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, and 20 μm, or is between any two values.

[0114] According to some embodiments of the present application, the present application provides a method for preparing the above-mentioned current collector, which includes: forming nanoparticles on at least one side of a copper foil body as a roughened surface.

[0115] The method of forming nanoparticles on at least one side of the copper foil body includes but is not limited to vapor deposition, in-situ growth and the like.

[0116] The above preparation method is simple and controllable to operate, and does not affect the strength of the copper foil body itself.

[0117] According to some embodiments of the present application, nanoparticles are grown in-situ in a liquid phase on at least one side surface of the copper foil body.

[0118] The liquid phase in-situ growth method is controllable and easy to industrialize, and the prepared nanoparticles are firmly bonded to the copper foil body, which is conducive to the long-term and stable bonding between the active material layer and the current collector, effectively improving the cycle performance.

[0119] According to some embodiments of the present application, at least one side of the copper foil body is immersed in a reaction solution for a liquid phase reduction reaction; wherein the reaction solution comprises: a mixed aqueous solution of 0.4-1.2 mol / L CuSO4 and 0.01-0.04 mol / L 1-butyl-3-methylimidazole halide.

[0120] The above-mentioned liquid phase reduction reaction method can effectively reduce the use of various acid and alkali pretreatment steps for commercial copper foil, reduce production costs and generate no waste acid and alkali, and has excellent deposition uniformity and processability. The deposition phase transition can be achieved by replacing a single ingredient in the formula, which is convenient for industrial production.

[0121] Optionally, the temperature of the liquid phase reduction reaction is 25-50° C., and the time of the liquid phase reduction reaction is 10-60 min.

[0122] The liquid phase reduction temperature is low and the time is short, and the preparation efficiency is high.

[0123] As an example, the temperature of the liquid-phase reduction reaction is any value among 25°C, 30°C, 35°C, 40°C, 45°C, 50°C or between any two values, and the time of the liquid-phase reduction reaction is any value among 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min or between any two values.

[0124] In addition to the above preparation methods, the method of in-situ growth of nanoparticles in liquid phase on at least one side of the copper foil body can also be: (a) immersing at least one side of the copper foil body in a copper chloride dihydrate reaction solution, using aloe powder extract as a reducing agent to perform a liquid phase reduction reaction to catalyze copper chloride dihydrate to generate CuCl. (b) immersing at least one side of the copper foil body in a reaction solution containing potassium bromide and copper chloride, using ascorbic acid as a reducing agent to perform a liquid phase reduction reaction to generate CuBr.

[0125] The aloe vera powder extract is prepared by adding aloe vera powder into deionized water, stirring and standing the mixture, and then centrifuging to obtain the supernatant.

[0126] The above two operations (a) and (b) may be specifically referred to in the relevant technology and are not limited here.

[0127] It should be noted that, in order to avoid interference from impurities, before performing the liquid phase in-situ growth, the preparation method further includes: cleaning the copper foil body with a first cleaning liquid, and then drying.

[0128] The cleaning solution includes deionized water or anhydrous ethanol. The drying can be carried out in an environment of 25-100°C or in an oven. Natural drying at room temperature can be selected to effectively save energy consumption.

[0129] In order to prevent impurities from interfering with the purity of the final prepared current collector, after the liquid phase in-situ growth, the preparation method further includes: cleaning the copper foil after the liquid phase in-situ growth with a second cleaning liquid, and then drying. The second cleaning liquid includes deionized water or anhydrous ethanol, and the drying can be air-dried in an environment of 25-100°C.

[0130] According to the above-mentioned liquid phase in-situ growth method, in order to achieve the continuous production of the roughened surface of the copper foil body on a large scale, such as Figure 5 As shown, the present application also provides a current collector preparation system 30, which includes: an unwinding mechanism 32 for automatically unwinding a copper foil 31 as a raw material, a soaking mechanism 33 for receiving the copper foil 31 unwound by the unwinding mechanism 32 and soaking the copper foil 31, the soaking mechanism 33 is equipped with a reaction liquid and an optional reducing agent, and a cleaning mechanism 34 for cleaning the copper foil 31 treated by the soaking mechanism 33, and a drying mechanism 35 for drying the copper foil 31 cleaned by the cleaning mechanism 34, and a winding mechanism 36 for winding the copper foil 31 dried by the drying mechanism 35, thereby forming an integrated automatic production mode of automatic unwinding-immersion deposition-cleaning-drying-winding.

[0131] According to some embodiments of the present application, the present application further provides a pole piece, which includes a current collector of any of the above schemes and an active material layer arranged on the surface of the current collector.

[0132] According to some embodiments of the present application, the present application also provides a battery, comprising a pole piece according to any of the above schemes.

[0133] According to some embodiments of the present application, the present application further provides an electrical device, comprising a battery according to any of the above schemes, and the battery is used to provide electrical energy to the electrical device.

[0134] The power-consuming device may be any of the aforementioned devices or systems using batteries.

[0135] According to some embodiments of the present application, the present application provides a current collector, which includes: a copper foil body, at least one side of the copper foil body is provided with a roughened surface composed of nanoparticles, the nanoparticles include CuX, wherein X is at least one of Cl, Br, and I, and the roughness of the roughened surface is: Ra: 0.784±0.01μm, Rz: 0.932±0.01μm, Rq: 3.278±0.02μm, the particle size of the nanoparticles is 400-500nm, and the height of the nanoparticles is 80-130nm.

[0136] Some specific embodiments are listed below to better illustrate the present application.

[0137] In the following embodiments and comparative examples, the thickness of the commercial electrolytic copper foil is 8 μm. The commercial electrolytic copper foil has a relatively rough surface and a smooth surface. The roughness of the smooth surface is: Ra: 0.683 μm, Rz: 0.820 μm, Rq: 3.135 μm, and the roughness of the matte surface is Ra: 0.740 μm, Rz: 0.890 μm, Rq: 3.254 μm.

[0138] Example 1

[0139] The preparation method of the current collector includes:

[0140] (1) Use anhydrous ethanol to clean the 6μm thick commercial electrolytic copper foil, dry it naturally after cleaning, and cut it into an area of ​​1*1cm 2 of copper sheet.

[0141] (2) Prepare 50 ml of a mixed aqueous solution of 0.4 mol / L CuSO4 and 0.01 mol / L 1-butyl-3-methylimidazolium bromide, stir until the solution is clear, immerse the pre-cleaned copper sheet completely in the solution, and let it stand for 10 minutes.

[0142] (3) Pick up the copper sheet with tweezers, rinse the copper foil three times with anhydrous ethanol, place it on a watch glass, dry it in a forced air drying oven at 60°C for 5 minutes, and then take it out.

[0143] Scanning electron microscopy and element distribution of the roughened surface of the current collector Figure 6 As shown, Figure 6The first row where (ab) is located is the roughened surface corresponding to the matte surface; the second row where (cd) is located is the roughened surface corresponding to the smooth surface.

[0144] according to Figure 6 It can be seen that after 10 minutes of solution immersion, CuBr nanoparticles are deposited on both the smooth and matte surfaces of the copper foil, with a particle size of about 500nm. Since the matte surface of the copper foil has a larger contact and reaction area, the deposited CuBr nanoparticles are denser than those on the smooth surface. The Br element response is consistent with the electron microscopy. Figure 1 This shows that this method can be used to successfully deposit nanoparticles on both smooth and matte surfaces.

[0145] Figure 7 for Figure 6 Cross-sectional scanning electron microscope images, where (a) is a cross-sectional scanning electron microscope image of the roughened surface corresponding to the matte surface; (b) is a cross-sectional scanning electron microscope image of the roughened surface corresponding to the smooth surface. Figure 7 It can be seen that the height of the nanoparticles is 330 nm.

[0146] Examples 2-10 and Comparative Example 1

[0147] The differences between the above embodiments and comparative examples and embodiments 1 and 2 are shown in Tables 1 and 2.

[0148] The only difference between Comparative Example 1 and Example 1 is that commercial electrolytic copper foil is directly used as the current collector.

[0149]

Cathode sheet preparation

[0150] LiNiCoMnO2 material, conductive carbon black and PVDF were added to NMP at a mass ratio of 97:1:2, and stirred to prepare slurry. The slurry was coated on aluminum foil, dried and cold pressed to obtain a positive electrode sheet.

[0151]

Negative electrode preparation

[0152] Graphite, acetylene black and polyvinylidene fluoride (PVDF) were mixed together in a mass ratio of 8:1:1 to form a mixture, and then fully ground in an agate mortar for more than 20 minutes. A certain amount of N-methylpyrrolidone (NMP) was added to the above mixture, and continued to be fully stirred. The obtained slurry was coated on the current collectors provided in each embodiment and comparative example, and then dried and cold pressed to obtain a negative electrode sheet.

[0153]

Electrolyte preparation

[0154] The electrolyte was prepared according to the following method: in an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were evenly mixed in a volume ratio of 3 / 7, 1 mol / L LiPF6 lithium salt was added and dispersed evenly, and then 2% fluoroethylene carbonate was dissolved in the above organic solvent and stirred evenly to obtain an electrolyte.

[0155]

Preparation of full battery

[0156] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried battery, and then after vacuum packaging, standing, forming, shaping and other processes, a full battery is obtained.

[0157]

Full battery cycle performance test

[0158] The battery prepared in the embodiment and the comparative example is first charged to 4.35V with a constant current of 1C, and then charged to a current of 0.05C with a constant voltage of 4.35V, and then discharged to 2V with a constant current of 1C. This is a charge and discharge cycle process, and the discharge capacity this time is the initial capacity C1. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time, and detect the discharge capacity of the 200th and 500th cycles. The battery capacity retention rate after each cycle is Pn = Cn / C1*100%. After 200 cycles, record C200, and calculate P200 = C200 / C1*100%. After 500 cycles, record C500, and calculate P500 = C500 / C1*100%.

[0159]

Half-cell preparation

[0160] Using a metal lithium sheet as a counter electrode, half cells were assembled using the negative electrode sheets of Example 1 and Comparative Example 1 in an inert atmosphere argon glove box.

[0161]

Half-cell electrochemical impedance spectroscopy test

[0162] The test frequency range of electrochemical impedance spectroscopy is 100mHZ-100kHz, and the amplitude voltage is 10mV.

[0163] The electrochemical impedance spectroscopy test results of Example 1 and Comparative Example 1 are as follows: Figure 8 As shown, according to Figure 8It can be seen that the charge transfer impedance of the copper foil current collector with in-situ deposited CuBr nanoparticles is basically the same as that of the rough surface of the untreated copper foil, and the charge transfer impedance of the copper foil current collector with in-situ deposited CuBr nanoparticles is about 250Ω lower than that of the smooth surface of the untreated copper foil. That is, the copper foil current collector with in-situ deposited CuBr nanoparticles can effectively improve the contact and charge transfer between the negative electrode graphite and the copper foil, helping the lithium battery to perform better. Figure 8 It can be seen that the charge transfer impedance of the copper foil current collector with in-situ deposited CuBr nanoparticles is the same as that of the rough surface of the untreated copper foil, that is, although the present application introduces non-copper nanoparticles CuBr, it still achieves the effect of pure copper.

[0164] The measurement results of the above-mentioned embodiments and comparative examples and embodiments 1 and 2 are shown in Table 1 and Table 2.

[0165] Table 1 Differentiating parameters

[0166]

[0167] Table 2 Distinguishing parameters and measurement results

[0168]

[0169] It can be seen from the embodiments and comparative example 1 that the roughening treatment method adopted in the present application is beneficial to reducing impedance and improving battery cycle retention rate.

[0170] It should be noted that in Example 1, since the pre-cleaned copper sheet is completely immersed in the solution, its matte surface is also roughened. The roughness of the roughened surface corresponding to the matte surface in Example 1 is: Ra is 0.813μm, Rz is 0.965μm, and Rq is 3.583μm. According to Example 1 and Comparative Example 1, it can be seen that the roughening treatment method of the present application can be used to roughen both the smooth surface and the matte surface. Although there is still a difference in the roughness of the roughened surface corresponding to the smooth surface and the matte surface after treatment, its impedance is significantly reduced compared to the untreated copper foil and the battery cycle retention rate is effectively improved.

[0171] According to Example 1 and Example 2, in Example 2, since only the smooth surface is roughened, the difference between the roughness of the smooth surface and the roughness of the matte surface becomes smaller, thereby further reducing the impedance and improving the cycle retention rate based on Example 1.

[0172] According to Examples 2 to 4, different roughening treatment times will affect the impedance of the current collector and the battery cycle retention rate, wherein the roughening treatment time of the light surface is within 60 minutes, especially 10-30 minutes, which can effectively reduce the impedance of the current collector and improve the battery cycle retention rate. Fig. 9This is a SEM image of the roughened surface provided in Example 3. Fig.10 This is a SEM image of the roughened surface provided in Example 4. Fig. 9 as well as Fig.10 It can be clearly seen that the particle size of the nanoparticles increases as the treatment time increases.

[0173] According to Examples 2, 5-7, the concentration of the reaction solution affects the performance of the current collector. When the reaction solution includes: 0.4-1.2 mol / L CuSO4, 0.01-0.04 mol / L 1-butyl-3-methylimidazole halide, the impedance of the current collector can be reduced and the battery cycle retention rate can be improved.

[0174] According to Examples 8-9, the reaction solution used is 1-butyl-3-methylimidazolium iodide, which can still reduce the impedance of the current collector and improve the battery cycle retention rate.

[0175] According to Examples 2-9, when one side of the copper foil body is a matte surface and the other side is a roughened surface, the roughness of the roughened surface is greater than that of the matte surface, and the difference in roughness between the roughened surface and the matte surface is: ΔRa≤0.196μm, ΔRz≤0.226μm, ΔRq≤1.622μm; further, ΔRa≤0.136μm, ΔRz≤0.177μm, ΔRq≤0.883μm; further, ΔRa≤0.113μm, ΔRz≤0.087μm, ΔRq≤0.474μm, having lower impedance and better battery cycle retention rate.

[0176] In Example 10, different roughening treatment times are used for the glossy surface and the matte surface. By extending the treatment time of the glossy surface to reduce the roughness difference between the two sides after the roughening treatment, the impedance is reduced and the battery cycle retention rate can be improved.

[0177] Fig.11 is a schematic diagram of cyclic stability, where Fig.11 The CuBr treated smooth surface current collector refers to the one side of the untreated rough surface and the CuBr side provided in Example 2; the untreated smooth surface: the untreated copper foil in Comparative Example 1, one side is smooth and the other side is rough. The untreated rough surface current collector: refers to the rough surface on both sides as shown in Comparative Example 1.

[0178] according to Fig.11 It can be seen that after the number of cycles exceeds 200, the cycle retention rate of the CuBr-treated smooth surface current collector is greater than that of the untreated rough surface current collector and greater than that of the untreated smooth surface current collector.

[0179] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A current collector, characterized in that: include: The copper foil body has a roughened surface composed of nanoparticles on at least one side, wherein the nanoparticles include CuX, wherein X is at least one of Cl, Br, and I.

2. The current collector according to claim 1, characterized in that: The particle size of the nanoparticles is 400-1000 nm, and can be optionally 400-700 nm.

3. The current collector according to claim 1, characterized in that: The height of the nanoparticles is 250-1520 nm, and can be optionally 320-840 nm.

4. The current collector according to any one of claims 1 to 3, characterized in that: One side of the copper foil body is a matte surface, and the other side is the roughened surface.

5. The current collector according to claim 4, characterized in that: The roughness of the roughened surface is greater than that of the matte surface, and the difference between the roughness of the roughened surface and the matte surface is: ΔRa≤0.196μm, ΔRz≤0.226μm, ΔRq≤1.622μm; The options are ΔRa≤0.136μm, ΔRz≤0.177μm, ΔRq≤0.883μm; Further options are ΔRa≤0.113 μm, ΔRz≤0.087 μm, and ΔRq≤0.474 μm.

6. The current collector according to any one of claims 1 to 3, characterized in that: The roughness of the roughened surface is: Ra: 0.784-0.936 μm, Rz: 0.928-1.116 μm, Rq: 3.272-4.876 μm.

7. The current collector according to any one of claims 1 to 4, characterized in that: The roughened surfaces are disposed on both sides of the copper foil body.

8. The current collector according to claim 7, characterized in that: The difference in roughness between the roughened surfaces on both sides is maintained at: ΔRa≤0.03 μm, ΔRz≤0.04 μm, and ΔRq≤0.4 μm.

9. The current collector according to any one of claims 1 to 8, characterized in that: The copper foil body has a thickness of 6-20 μm.

10. The method for preparing a current collector according to any one of claims 1 to 9, characterized in that: include: The nanoparticles are formed on at least one side surface of the copper foil body as the roughened surface.

11. The preparation method according to claim 10, characterized in that: The nanoparticles are in-situ grown in a liquid phase on at least one of the side surfaces of the copper foil body.

12. The preparation method according to claim 10 or 11, characterized in that: Immersing at least one side surface of the copper foil body in a reaction solution to perform a liquid phase reduction reaction; Wherein, the reaction solution comprises: a mixed aqueous solution of 0.4-1.2 mol / L CuSO4 and 0.01-0.04 mol / L 1-butyl-3-methylimidazolium halide; Optionally, the temperature of the liquid phase reduction reaction is 25-50° C., and the time of the liquid phase reduction reaction is 10-60 min.

13. A pole piece, characterized in that: The invention comprises the current collector according to any one of claims 1 to 9 and an active material layer arranged on the surface of the current collector.

14. A battery, characterized in that: Including the pole piece as claimed in claim 13.

15. An electrical device, characterized in that: The battery according to claim 14 is used to provide electrical energy.